Terminal Assessment of Core Nursing Knowledge in a State University - Rosana Grace Belo-Delariarte; Ryan Michael F. Oducado; Ayesha C. Penuela (Asia Pacific Journal of Multidisciplinary Research, 2018)
Assessment of educational outcomes upon completion of the nursing program is one way to inform academic institutions of the effectiveness of their teaching-learning practices. A descriptive correlational study design was carried out among 141 graduating nursing students of West Visayas State University to assess their terminal cognitive competency on core nursing knowledge framed under the National Nursing Competency Standards' 11 Key Areas of Responsibility. All regular graduating students in the year 2015 with complete records of secondary data needed for the study were included. A validated and reliability tested questionnaire was used to assess the terminal core nursing knowledge competencies of the students. Results revealed that students, prior to graduation, had good core nursing knowledge. Significant differences were found in the terminal core nursing knowledge of students when grouped according to Nursing Aptitude Test (NAT) and academic performance in professional nursing courses, with students who had excellent and superior NAT performance and those with very good and outstanding academic performance in professional nursing courses having significantly higher terminal core nursing knowledge. NAT and academic performance had significant, positive correlation to core nursing knowledge. Further, NAT and academic performance accounted for 46% of variance explained in the core nursing knowledge of nursing students. Higher Education Institutions, therefore, must commit themselves in providing quality nursing education by ensuring proper, responsive and relevant implementation of the nursing curriculum. This in turn may translate to attainment of intended educational outcomes and learners knowledgeable of the basic foundation of nursing practice.
Keywords: 330; competency assessment; terminal assessment; outcomes assessment; terminal competency; nursing students; nursing education; key areas of responsibility; core competency standards